Increase of Physical Activity of Primary School Students With Cheerleading Means - Olha Kolomeitseva (Lesya Ukrainka Volyn National University, 2017)
Revelance of research is due to gain trend of worsening health of primary school students and necessity of search of innovative forms of modernization of system physical education in conditions of reforming the education system. The purpose of research is to experimentally substantiate the effectiveness of cheerleading practices as mean of increasing physical activity of primary school students in the process of extracurricular physical educative and sports work. Based on the generalization of scientific literature on the research problem found out, that cheerleading practices contribute to the effective functioning of the body's basic systems, formation of vital physical skills, increasing of physical preparation level, perfection of physical qualities. Proposed the program of cheerleaders' physical preparation with the purpose of increasing the level of their physical activity, where 50 % of the practice time is allocated to general physical training with a priority direction of development of endurance, strength, flexibility, coordination skills, dexterity in the process of both specially organized and substantive cheerleading practices. According to the results of the initial and control stages of diagnosis based on standardized tests (broad jump, jumps through the gymnastic bench on two legs for 10 seconds, lifting the torso from a prone position, flexion of the torso from sitting position, push-ups) proved that systematic practices contributed to an increase of physical development indicators and physical preparedness of students by 25 %. It has been proved, that cheerleading practices, as a model for improving children` health physical regime of primary school students, provide necessary amount of physical activity to pupils during extracurricular physical educative and sports work.